Diabetes and keratotic lesions of lichen planus - F. Agha hoseini; N. Moghadam (Tehran University of Medical Sciences, 1998)
In 1996 Grinspan et al presented the association between primary hypertension and diabetes mellitus as Grinspan Syndrome. Through various studies, Researchers have noticed that epidermal lichen planus cells show enzymatic disorders as well as defective carbohydrate expression. Therefore, it was assumed that there is a relationship between cells and hormones in metabolic actions. Besides, some researchers presented the possible relation between hormonal dysfunction and immunological disorders leading to lichen planus development. It was found that primary hypertension is not related to lichen planus and lichen planus is presented in hypertensive patients as a result of antihypertensive medications. Therefore, the majority of studies in this regard have been focused on diabtese and lichen planus, their prevalence , comparing patients with the control groups and the association between blood sugar, blood fats , antihypertensive drugs and lipid lowering drugs.